Low Multiplicity of HIV-1 Infection and No Vaccine Enhancement in VAX003 Injection Drug Users. (14th August 2014) - Sterrett, Sarah; Learn, Gerald H.; Edlefsen, Paul T.; Haynes, Barton F.; Hahn, Beatrice H.; Shaw, George M.; Bar, Katharine J.
Abstract: Background. We performed human immunodeficiency virus type 1 (HIV-1) transmitted/founder (T/F) virus analysis of the VAX003 vaccine efficacy trial participants to characterize the transmission bottleneck and test for vaccine-associated reduction or enhancement of infection in this injection drug user (IDU) cohort. Methods. We performed single genome sequencing of plasma vRNA from 50 subjects sampled in early HIV infection. Sequences were analyzed phylogenetically, T/F viruses enumerated, and a sieve analysis performed. Results. Eight of 19 (42%) placebo recipients were productively infected by more than 1 virus (range 1–5, median 1, mean 1.7). This frequency of multiple virus transmission was greater than reported for heterosexual cohorts (19%, P = .03) but not statistically different from vaccine recipients (22.6%, P > .05), where the range was 1–3, median 1, and mean 1.3 ( P > .05 for all comparisons). An atypical sieve effect was detected in Env V2 but was not associated with reduction or enhancement of virus acquisition. Conclusions. The number of T/F viruses in IDUs was surprising low, with 95% of individuals infected by only 1–3 viruses. This finding suggests that a successful vaccine or other prevention modality generally needs to protect against only one or a few viruses regardless of risk behavior. T/F analysis ide.jpegied an atypical genetic sieve in the V2 region of Envelope and found no evidence for vaccine-mediated enhancement in VAX003.